16S rRNA-based Metagenomic Analysis of Endophytic Actinomycetes Diversity from Tinospora crispa L. Miers - MONA PRIMANITA; ARIS TRI WAHYUDI; YULIN LESTARI (Microbiology Indonesia, 2015)
Endophytic actinomycetes associated with medicinal plants is very important as source of various bioactive compounds. The fact that more than 99% of microbes that exist in nature may have the potency but still unexplored. Published data regarding diversity of endophytic actinomycetes from T. crispa is mainly based on a culturable approach. This paper describes the first reported data regarding metagenomic analysis on the diversity of endophytic actinomycetes from T.crispa based on 16S rRNA gene using PCR-DGGE. There were some similarities amongst endophytic actinomycetes found in stems, roots, and leaves with soil actinomycetes community in the rhizosphere of T. crispa. There were a total of 21 bands found from the DGGE analysis which were interpreted using Phoretix 1D software. Diversity of actinomycetes in the stems, leaves, roots were represented by 17, 16, and 14 bands, respectively. Whereas only 10 bands represented diversity of actinomycetes in the soil rhizosphere. The 12 dominant and or different bands with 180 bp in size were molecularly sequenced. The A4 and A9 bands have 95% and 86% similarities with Williamsia and Streptomyces, respectively. These similarities were less than 97% thus may indicate novel actinomycetes. The other 10 sequenced bands have closed similarity ranging from 97-100% and they were closely related to the genus Streptomyces, Microbacterium, Amycolatopsis, Actinomadura, Actinoplanes, Actinokineospora, Kibdelosporangium, Williamsia and Kocuria. These findings indicate that diversity of actinomycetes can be found associated with T. crispa.Â